2023
DOI: 10.3390/jpm13040652
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BDNF as a Biomarker in Cognitive and Sensory Neurodegeneration

Abstract: Brain-derived neurotrophic factor (BDNF) has a crucial function in the central nervous system and in sensory structures including olfactory and auditory systems. Many studies have highlighted the protective effects of BDNF in the brain, showing how it can promote neuronal growth and survival and modulate synaptic plasticity. On the other hand, conflicting data about BDNF expression and functions in the cochlear and in olfactory structures have been reported. Several clinical and experimental research studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 287 publications
0
11
0
Order By: Relevance
“…The NeuN-related neurodegeneration induced by PTZ can be ameliorated through supplementation with DHA and EPA, in which EPA showed superiority ( Figure 4 A). Brain-derived neurotrophic factor (BDNF), is a biomarker of neuronal plasticity and plays a critical role in neuronal development and function [ 19 ]. The protein levels of BDNF obviously declined in the PTZ group compared with that of the Con group, while supplementation with EPA and DHA similarly increased the levels of BDNF ( F = 23.61, p = 0.0003).…”
Section: Resultsmentioning
confidence: 99%
“…The NeuN-related neurodegeneration induced by PTZ can be ameliorated through supplementation with DHA and EPA, in which EPA showed superiority ( Figure 4 A). Brain-derived neurotrophic factor (BDNF), is a biomarker of neuronal plasticity and plays a critical role in neuronal development and function [ 19 ]. The protein levels of BDNF obviously declined in the PTZ group compared with that of the Con group, while supplementation with EPA and DHA similarly increased the levels of BDNF ( F = 23.61, p = 0.0003).…”
Section: Resultsmentioning
confidence: 99%
“…Neurotrophins, such as NT3 and BDNF, have been extensively studied for their central and peripheral neuroprotective effects. ( 27 , 28 ) However, their clinical application presents challenges owing to their short plasma half-life (1.28 and 0.92 min for NT3 and BDNF, respectively) after intravenous administration. ( 29 ) To overcome these limitations, the potency of adeno-associated virus (AAV) gene therapy to increase intracellular NT3 levels has been explored for several diseases, including sarcopenia, ( 30 ) Charcot-Marie-Tooth disease, ( 31 ) and cochlear synaptopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The critical involvement of BDNF/TrkBmediated signaling, such as phospholipase Cγ (PLCγ)-, PI3k/Akt-, and ERK-signaling in the neuro-and glio-genesis, as well as in synaptic function, is highlighted [4]. As expected, in addition to experimental research studies, clinical evidence also shows that the alteration in BDNF levels in neurodegenerative diseases can be a promising biomarker in most neurodegenerative conditions and neurodegenerative diseases, including Alzheimer's disease (AD) [5]. Furthermore, it has been demonstrated that apoptotic elements, which are considered responsible for manifestations linked to the pathophysiology of AD, interact with various signaling molecules, including BDNF/TrkB, and downstream signaling pathways [6].…”
Section: Introductionmentioning
confidence: 88%